Artificial intelligence and digital twins - Bondarenko, I.; Karnaushenko, V.; Olexiy Pashchenko (ХНУРЕ, 2025)
Robots and AI-based software can be expensive, delaying adoption in some industries. In addition, AI tools are not always ready for mission-critical applications because there are not enough data sets to train them. One of the important factors in the development of cyber-physical systems is the use of digital twin technology. As embedded vision systems, sensors, and AI pipelines become increasingly complex, digital twins will continue to be the testing ground where the robotic accounting of the future are created today.
Keywords: digital twins; artificial intelligence; robotics